Array - Zaman, Achmad Qomaruz; Listiadi, Agung (Jurnal Pendidikan Akuntansi (JPAK), 2022)
The development of science and technology has an impact on teaching and learning activities. Educators are required to make teaching and learning activities more varied so that students can play an active role during teaching and learning activities. Learning media can be an alternative for educators to create student participation during teaching and learning activities. Based on observations made by researchers, it was found that the media that had been used by accounting teachers at SMKN 6 Surabaya, especially in the accounting department, still depended on power points and lacked use of developed technology. This study has a goal to create an android-based accounting learning media for students of class XI Accounting at SMKN 6 Surabaya and see how feasible Android-based accounting learning media is as a creative medium in the accounting practicum learning process for service, trade, and manufacturing companies. In developing learning media using the 4D model by Thiagarajan which consists of the definition stage (Define), the design stage (Design), the development stage (Develop), and the dissemination stage (Disseminate). Data collection techniques were in the form of validation questionnaires and student response questionnaires related to the developed media. The results of the evaluation carried out by material experts and media experts, Lakeun’s learning media can be said to be feasible, as well as student responses regarding the learning media made also obtain very understood criteria.